Beneficial Brain Drain and Non-Migrants' Welfare - Maurice Schiff (Institute of Labor Economics (IZA), 2018)
Though a net brain gain has tended to be seen as a benefit and referred to as a 'beneficial brain drain' in the literature, its welfare impact for source country residents – or non-migrants – is at best ambiguous. Increased educational investment in response to a brain drain is equivalent to a bet where migrants (M) win and where the impact on residents (R) – whose well-being is a concern for the government – is ambiguous or negative. I compare residents' welfare a) for an open vs. a closed economy, b) under the presence or absence of education externality, c) with vs. without government intervention, and d) with government's concern equal for R and M (R = M) or greater for R (R > M). Main findings are: i) residents lose under an open economy in four of the five scenarios considered, with an ambiguous result under an externality and no intervention; ii) optimal education policy has a positive or ambiguous impact on residents' welfare (and a positive impact under a closed economy); and iii) welfare is higher under intervention when R > M than when R = M. It is worth noting that, though the standard developing country policy of subsidizing higher education is optimal under an education externality in the case of a closed economy, this result need not hold under an open economy.
Keywords: F22; I20; J61; 330; brain drain; net brain gain; education policy; source country residents; welfare